Short-term growth during treatment with inhaled fluticasone propionate and beclomethasone dipropionate. - Wolthers, O D (1993)
Short-term lower leg growth was investigated with twice weekly knemometry measurements in 19 schoolchildren with mild asthma during treatment with daily doses of 200 micrograms fluticasone propionate, 400 micrograms, and 800 micrograms beclomethasone dipropionate from a dry powder inhaler. The design was a randomised, double blind, crossover trial. After a run in period of four days (period 1) the children were allocated to a sequence of active treatments in periods 2, 4, and 6. In periods 3 and 5 (wash out) placebo was given. All periods except the run in were two weeks long. The mean lower leg growth velocities during the wash out periods were 0.61 and 0.80 mm/week. Mean growth velocities during treatment with fluticasone propionate and low and high doses of beclomethasone dipropionate were 0.34, 0.09, and 0.06 mm/week respectively. Compared with fluticasone propionate, treatment with beclomethasone dipropionate 400 and 800 micrograms/day was associated with a statistically significant reduction in growth velocity.